Performance Evaluation and Clinical Associations of Immunoassays That Detect Antibodies to Negatively Charged Phospholipids Other Than Cardiolipin. Issue 5 (14th March 2018) - Castanon, Amaris; Pierre, Grant; Willis, Rohan; Harris, E Nigel; Papalardo, Elizabeth; Romay-Penabad, Zurina; Schleh, Alvaro; Jajoria, Praveen; Smikle, Monica; DeCeulaer, Karel; Tebo, Anne; Jaskowski, Troy; et al.
Abstract: Objectives: We evaluate the performance characteristics of antiphosphatidylserine (anti-PS), antiphosphatidylinositol (anti-PI), and antiphospholipid mixture (APhL) enzyme-linked immunosorbent assays (ELISAs) compared with anticardiolipin (aCL) and anti–β2 glycoprotein I (anti-β2GPI) in a large group of patients with antiphospholipid (aPL)–related diseases. Methods: Serum samples from 548 patients from the Hopkins and Jamaican systemic lupus erythematosus cohorts, the PROMISSE cohort, and the Antiphospholipid Standardization Laboratory were examined for immunoglobulin G (IgG)/immunoglobulin M (IgM) positivity in aCL, anti-β2GPI, anti-PS, anti-PI, and APhL ELISA assays. Results: All IgG assays were associated with one or more thrombotic and/or obstetric manifestations, with an increased risk associated with higher antibody titers. Analytical performance was similar among assays, but IgG assays performed better than IgM counterparts. Conclusions: Increasing titers of APhL, anti-PS, and anti-PI antibodies could indicate an increased risk of thrombotic and/or obstetric aPL-related manifestations. These assays may be promising biomarkers for particular APS manifestations.